Social withdrawal behavior in institutionalized toddlers: individual, early family and institutional determinants - Baptista, J.; Belsky, J.; Martins, C.; Silva, J. R.; Marques, S.; Mesquita, A.; Soares, I. (Infant Mental Health Journal, 2013)
Eighty-five Portuguese children, aged 12 to 30 months, placed in residential institutions were assessed to investigate the influence of variations in the institutionalization experience of social withdrawal behavior, after taking into account potentially confounding individual characteristics and pre-admission experiences. In light of the limited attention in institutionalization research on social withdrawal, the determinants of the identified predictors of withdrawal symptoms also were examined. Current quality of care experienced in the institution, operationalized in terms of the absence (vs. presence) of a preferred attachment relationship, predicted social withdrawal, such that absence of such a relationship forecasted greater withdrawal.Moreover, existence of a preferred attachment relationship was itself predicted by better child socioemotional functioning, greater caregiver sensitive-responsiveness, and better quality of individualized care provided by the staff.